2016
DOI: 10.7860/jcdr/2016/14802.7716
|View full text |Cite
|
Sign up to set email alerts
|

Helicobacter pylori in Cholecystectomy Specimens- Morphological and Immunohistochemical Assessment

Abstract: Helicobacter pylori is present in gall bladder and is commonly seen in association with stones. A more detailed study of cholecystectomy cases (both neoplastic and non-neoplastic) with serological, culture and molecular data of H.pylori is desirable to study the pathogenesis of cholecystitis, its association with gall stones and other gall bladder disorders.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
4
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 15 publications
2
4
1
Order By: Relevance
“…In contrast to many studies, a retrospective study 15 of 45 cases including cholecystectomy samples detected H. pylori -positivity in the gallbladder in 40% of patients without gallstones and 20% of those with gallstones. However, this difference was not significant and no relationship could be established between H. pylori -positivity and the occurrence of gallstones.…”
Section: Discussioncontrasting
confidence: 65%
See 3 more Smart Citations
“…In contrast to many studies, a retrospective study 15 of 45 cases including cholecystectomy samples detected H. pylori -positivity in the gallbladder in 40% of patients without gallstones and 20% of those with gallstones. However, this difference was not significant and no relationship could be established between H. pylori -positivity and the occurrence of gallstones.…”
Section: Discussioncontrasting
confidence: 65%
“…Moreover, no H. pylori gallbladder infection was noted in 10 patients with ulceration of the gallbladder. 15 Similarly, the current study found no relationship between H. pylori -positivity in the gallbladder and gallstones, or the development of cholesterolosis, intestinal metaplasia, pyloric metaplasia, and activation.…”
Section: Discussionsupporting
confidence: 56%
See 2 more Smart Citations
“…This gram-negative rod has previously been associated with gastritis and acid peptic disease 8 for decades and studies have been carried out to show its association with gallstones, cholecystitis 13,14 and gall bladder cancer. 15 Many serological and histological methods 16,17 have been used to detect its presence in gall bladder mucosa and bile including Giemsa staining, H&E, PCR, Urease test, Warthin-starry 18 test etc. Out of these Giemsa and H&E are considered the simplest, cheapest and most specific methods.…”
Section: Original Articlementioning
confidence: 99%